Mixed mode fracture: numerical evaluation and experimental validation using PMMA specimens - Sérgio Alexandre Gonçalves Pereira; Sérgio M.O. Tavares; Paulo M.S.T. de Castro (Fracture and Structural Integrity)
Mixed mode crack propagation analysis has been more accessible with the development of new numerical tools, allowing to evaluate the influence of non-mode I loadings in the crack path and in the growth rate. The aim of this work is to analyse the propagation of pre-existing cracks under pure mode I, pure mode II and unstable mixed mode I-II loading conditions. Numerical simulations with two-dimensional models created in Abaqus software were performed, and the results obtained were compared with the analytical and experimental results. To determine T-stress and stress intensity factors, the conventional finite element method was used, post-processed with the modified virtual crack closure technique (mVCCT) and / or the J-integral. The extended finite element method (XFEM) is also used to predict the crack trajectory under different loading conditions. The experimental procedures were performed in three and four-point bending tests on single edge notch specimens of PMMA, in which a natural pre-crack was created by small impacts with a hammer on a blade located over the pre-existing machined notch. The four-point bending test was performed with an asymmetrical configuration. Varying the locations of supports and loading points with respect to the crack plane, this configuration allows to create pure mode II and mixed-mode I-II situations. The three-point bending test was performed in the conventional manner, with only the distance from the load line to the crack plane being varied.